The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1021/acs.analchem.1c02191
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Sensitivity of the Virus BioResistor by Overoxidation: Detecting IgG Antibodies

Abstract: The Virus BioResistor (VBR) is a biosensor capable of rapid and sensitive detection of small protein disease markers using a simple dip-and-read modality. For example, the bladder cancer-associated protein DJ-1 (22 kDa) can be detected in human urine within 1.0 min with a limit of detection (LOD) of 10 pM. The VBR uses engineered virus particles as receptors to recognize and selectively bind the protein of interest. These virus particles are entrained in a conductive poly(3,4-ethylenedioxythiophene) or PEDOT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Despite the fact that this type of biosensing is noninvasive and research is being conducted on nonenzymatic forms of detection, such as cholesterol detection, the current market uses an enzymatic form of detection, which has some drawbacks in the form of fluctuations in conductivity due to enzymatic reactions and the conductivity of the electrolyte solution [ 76 ]. Okafor et al, proposed a conductometric biosensor based on polyaniline (PANI) for the detection of Johne’s disease-specified IgG antibodies [ 77 ]. This sensor was further compared with the detection of IgG with ELISA, and this study confirmed the moderate agreement between both techniques [ 78 ].…”
Section: Biosensors For the Detection Of Iggmentioning
confidence: 99%
“…Despite the fact that this type of biosensing is noninvasive and research is being conducted on nonenzymatic forms of detection, such as cholesterol detection, the current market uses an enzymatic form of detection, which has some drawbacks in the form of fluctuations in conductivity due to enzymatic reactions and the conductivity of the electrolyte solution [ 76 ]. Okafor et al, proposed a conductometric biosensor based on polyaniline (PANI) for the detection of Johne’s disease-specified IgG antibodies [ 77 ]. This sensor was further compared with the detection of IgG with ELISA, and this study confirmed the moderate agreement between both techniques [ 78 ].…”
Section: Biosensors For the Detection Of Iggmentioning
confidence: 99%
“…To address this limitation, the PEDOT channel of the VBR is subjected to a simple electrochemical process called potentiostatic overoxidation, which reduces the conductivity of the polymeric channel. 73 The resulting biosensors, known as O 2 VBRs, exhibit enhanced sensitivity to both small and large proteins. For instance, two undetectable antibodies at normal VBRs can be detected using O 2 VBRs with a limit of detection of 40 ng/mL and a dynamic range for quantitation extending to 600 ng/mL.…”
Section: Conductometric Igg Biosensorsmentioning
confidence: 99%
“…Viral bioresistance (VBR), as a biosensor, employs virion as a receptor to rapidly and sensitively detect small protein disease indicators via a simple dip-and-read method (Bhasin et al, 2021). Typically, this technology utilizes biomarker-binding moiety-engineered VBR viruses that are incorporated into films of electronically conductive polymers, such as poly-3,4-ethylenedioxythiophene (PEDOT).…”
Section: Electric Signalmentioning
confidence: 99%
“…Once the virions recognized and captured the electrical insulating DJ-1, the conductivity of the resistance channel would decrease, resulting in a LOD of 10 pM (Figure 3b). Unfortunately, the VBR seems to be insensitive to larger molecular proteins (Bhasin et al, 2021). To address this issue, Jia et al presented a new direct detection method for large cancer markers or even cancer cells based on phage-light addressable potentiometric sensing (LAPS; Jia et al, 2007).…”
Section: Electric Signalmentioning
confidence: 99%